Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.2459/jcm.0b013e3283590d3d
|View full text |Cite
|
Sign up to set email alerts
|

Impaired microvascular endothelial function in vitamin D-deficient diabetic nephropathy patients

Abstract: Microvascular endothelial function was significantly reduced in diabetic nephropathy patients with deficient vitamin D levels compared with those with nondeficient levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Similarly, Yildirim et al [ 29 ] also confirmed that 1,25-(OH) 2 D 3 could downregulate the protein expression of VEGF, thereby reducing angiogenesis and inflammation. Compared to DKD patients with normal vitamin D levels, those with vitamin D deficiency have decreased microvascular endothelial function [ 30 ]. Vascular endothelial injury leads to adhesion and activation of inflammatory cytokines, which may increase the expression of vWf and further promote DKD process.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Yildirim et al [ 29 ] also confirmed that 1,25-(OH) 2 D 3 could downregulate the protein expression of VEGF, thereby reducing angiogenesis and inflammation. Compared to DKD patients with normal vitamin D levels, those with vitamin D deficiency have decreased microvascular endothelial function [ 30 ]. Vascular endothelial injury leads to adhesion and activation of inflammatory cytokines, which may increase the expression of vWf and further promote DKD process.…”
Section: Discussionmentioning
confidence: 99%
“…Iontophoresis is a method of introducing charged substances across the skin using a weak electrical current. The iontophoresis protocol used in this study was as per our previous study . The parameter used to assess microvascular endothelial function was maximum absolute change in perfusion due to ACh iontophoresis (ACh max ).…”
Section: Methodsmentioning
confidence: 99%
“…The primary parameter of interest in this study was microvascular endothelial function, and therefore our calculation of sample size was based mainly on this parameter. We calculated sample size for microvascular endothelial function based on our previous study, with 90% power at α of 0.05 to detect a difference of 13.7 AU at a standard deviation of 14.8 AU . A minimum of 25 subjects were required in each group to complete the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, an association between VD and vascular function has been described in patients with diabetes [93]; moreover, a report described improved vascular function parameters in patients with diabetes, after VD oral supplementation [94]. Furthermore, in patients with diabetes and VD deficiency reduced endothelium-dependent microvascular function, assessed by iontophoresis of acetylcholine, when compared to patients with diabetes and non-deficient VD levels [95]. Experimental studies have shown that VD improves endothelial dysfunction and promotes vascular regeneration through the activation of VDR, that in turn regulates the expression of numerous genes involved in fundamental processes of potential relevance to cardiovascular function [96]; in fact, the suppression of VDR in endothelial cells (EC) alters vascular homeostasis [1,97].…”
Section: General Mechanisms Of Vd Vascular Protection In Diabetesmentioning
confidence: 99%